Partial Resection Versus Preservation of Middle Turbinate in Surgery for Chronic Rhinosinusitis with Nasal Polyposis - Maitham Talib Jbarah; Azaam Muhsin Abbas (University of Kirkuk, College of Medicine, Kirkuk, Iraq, 2024)
Background: The Ostiomeatal Complex (OMC) is a functional concept rather than an anatomic structure with defined boundaries. The aim of this study is to compare between partial resection of middle turbinate and middle turbinate preservation in surgery for chronic rhinosinusitis with nasal polyposis.Methods: This prospective interventional study was conducted on two groups of patients diagnosed with chronic rhinosinusitis with nasal polyposis who did not respond to medical treatment. These patients underwent endoscopic sinus surgery and were categorized into two groups. Group A with bilateral resection of the middle turbinate and group B with careful preservation, The follow-up period extended up to three months after surgery.Results: Total mean age (39 ±14) years. At the end of the follow-up period, the patency of the middle meatal antrostomy was (96.15%) in group A and (73.08%) in group B. The adhesion was 7.7% in group A and 23% in group B, at the end of the first postoperative month the crustation was 76% in group A and 61.5% in group B and at the end of follow-up there is an improvement in nasal obstruction in both groups with a significant improvement in group A (p-value= 0.017).Conclusion: Partial resection of the middle turbinate during endoscopic sinus surgery improves the patency of the middle meatal antrostomy, better access, and improved ability for endoscopic clearance and debridement of the crustation postoperatively, also associated with a lower risk of adhesion to the lateral nasal wall and a significant improvement in postoperative nasal obstruction compared to patients who undergo endoscopic sinus surgery with preservation of themiddle turbinate.